Pendampingan Pembentukan Karakter Nasionalis-Religius dalam Giat Rotibul Haddad dan Semarak Agustus 2025 di Desa Gunung Malang, Kecamatan Sumberjambe, Kabupaten Jember - Hasbi Ash Shiddiqi; Sofiatus Sobriyah (Universitas Respati Indonesia, 2026)
Assistance in the formation of nationalist-religious character is an urgent need in the midst of the challenges of globalization, modernization, and the rapid flow of digitalization that has the potential to erode the values of nationality and the spirituality of society. This service activity aims to assist the people of Gunung Malang Village, Sumberjambe District, Jember Regency in strengthening the nationalist-religious character through the religious activities of Rotibul Haddad and the August 2025 Vibrant celebration. The approach used is Participatory Action Research (PAR) by emphasizing active community participation from the planning, implementation, to evaluation stages of activities. Emile Durkheim's theoretical perspective is used to analyze the role of collective rituals and social practices in creating mechanical solidarity that strengthens social cohesion as well as fosters nationalist-religious consciousness. The results of the mentoring show that Rotibul Haddad activities are routinely able to foster a deep sense of religiosity and spirituality, while the August Celebration with various competitions and celebrations strengthens nationalism and a sense of togetherness across generations. The integration of the two gives birth to harmony between religious and national values which is reflected in increasing community participation, social solidarity, and collective awareness of maintaining local traditions within the framework of the Republic of Indonesia. The significance of this activity lies in strengthening the social base of the village community which is able to make religion and nationalism not as separate entities, but as a complementary foundation in building the character of the nation. Thus, this assistance not only results in transformation at the individual level, but also strengthens the social cohesion of the people of Gunung Malang Village as a model for strengthening the nationalist-religious character based on local wisdom.